2-Deoxy-d-glucose functionalized zinc oxide nanodrug for kidney cancer treatment - Y.S. Vidya; H.C. Manjunatha; S. Manjunatha; K.N. Sridhar; L. Seenappa; R. Munirathnam (Journal of Science: Advanced Materials and Devices, 2023)
For the first time, zinc oxide (ZnO) nanoparticles (NPs) are synthesized by the green combustion method using apple peel extract as a reducing agent. Further, ZnO-Deoxy-d-Glucose (2DG) nanohybrids were synthesized by the sputtering method. These synthesized biomolecule-coated NPs and nanohybrids are characterized with different techniques. The Bragg reflections confirm the hexagonal Wurtzite structure for ZnO. A decrease in crystallite size and an increase in energy band gap were observed for ZnO and ZnO-2DG. The tuning of the band gap plays a vital role in cytotoxicity, arbitrated by intracellular reactive oxygen species. The cytotoxic properties, such as the percentage of inhibition and the percentage of the proliferation of ZnO and ZnO-2DG nanohybrid, are examined against the Kidney cancer Vero cell line and also compared with the standard drugs Levofloxacin and Doxorubicin. Compared to ZnO, ZnO-2DG shows excellent cytotoxic properties, even better than the standard drug against the Vero cell line. Thus, the present ZnO-2DG nanohybrid might be used as a nanodrug and go on to replace Levofloxacin and Doxorubicin as standard drugs in kidney cancer cell therapy.